THE USE OF GENERATIVE ARTIFICIAL INTELLIGENCE (AI) FOR UNIVERSITY STUDENTS - Muhammad Argi Rahmadi; Dimas Ujang Susilo; Retno Widyani; Djohan Rochanda Wiradinata (Jurnal Abdisci, 2025)
Background. The development of information technology has been very rapid lately. Aims. Artificial intelligence has replaced the function of the human brain in collecting and processing data. This is very useful in making it easier for students to compile scientific papers and complete the final project through reports and theses. Counseling has been carried out for students to understand the important role and obstacles that must be watched out for in using AI technology. Method. The method used is a PowerPoint presentation, which is done by the student group and accompanied by a lecturer as a resource person. Result. The material presented covered the potential and challenges of using Generative AI (GenAI) in learning in higher education, as well as providing practical and ethical guidance to utilize this technology responsibly. The AI competency framework for students consists of 3 levels. First, I need to understand AI technology; second, I need to use AI responsibly; and third, I need to evaluate AI results critically. Examples of Gen Ai applications: ChatGPT helps create task drafts and provide ideas; Grammarly checks grammar and writing style; DALL-E creates a design or presentation fiscal illustration. The conclusion and hope that can be put forward in this activity is that GenAI is a tool that can enrich the learning process, but it is important to use it ethically and responsibly. With a good understanding, GenAI can be a partner in creating innovative and effective learning. Consclusion. Because ChatGPT offers benefits in accessibility, speed, and originality, it has unquestionably changed the way students approach academic assignments. However, when misused, it can compromise critical thinking and academic integrity.